ASSESSING PM2.5 EMISSION REDUCTION THROUGH COMMUNITY GREEN BEHAVIOR IN EAST JAKARTA: A SYSTEM DYNAMICS APPROACH - Chaisya Wilver; Wilma Nurrul Adzillah; Aries Purwanto (Lingkar: Journal of Environmental Engineering, 2026)
East Jakarta faces a severe PM₂.₅ air quality crisis, with concentrations reaching 147.64 µg/m³ nearly ten times the national standard of 15 µg/m³. This study quantifies the potential of community green behavior to reduce PM₂.₅ emissions through a system dynamics approach. Data from 100 respondents collected through proportional quota sampling were extrapolated to the East Jakarta household population (867,399 households) and incorporated into a Vensim PLE simulation model. The baseline inventory revealed total PM₂.₅ emissions of 952.86 ton/year, dominated by the waste sector (85.6%), while vegetation absorbs only 102.78 ton/year, leaving a net deficit of 850.08 ton/year. The community Green Behavior Index (GBI) averaged 2.67 out of 5 (moderate); waste management registered the lowest GBI (2.30) despite its highest emission share, revealing a structural behavioral paradox. Four scenarios at moderate (GBI = 3.4) and optimistic (GBI = 4.2) intervention levels were simulated. The best case scenario achieved 23.36% emission reduction, with waste related behavior contributing 62.4% of that potential. Under the optimistic full sector scenario, emission absorption equilibrium is projected between 2035 and 2044, compared to approximately 2050 under Business as Usual. Green behavior is necessary but not sufficient; structural interventions remain essential.